Effects of Remifentanil and Dexmedetomidine with Propofol on Laryngeal Mask Airway Insertion, Hemodynamic Stability, and Pharyngolaryngeal Morbidity: A Prospective Study of 80 Patients - Çakırgöz, Mensure; Demirel, İsmail; Akan, Mert; Alaygut, Ergin; Saraç, Ömürhan; Kar, Aysun Afife; Yurtlu, Derya Arslan (International Scientific Information, Inc., 2025)
Background: Propofol is the most commonly used hypnotic for laryngeal mask airway (LMA) insertion but requires high doses when used alone, potentially causing cardiorespiratory depression. Muscle relaxants are recommended, yet no study has assessed the effects of remifentanil and dexmedetomidine before propofol induction on LMA insertion conditions. This prospective study aimed to compare the outcomes of propofol administered with remifentanil versus dexmedetomidine during short-duration operations requiring LMA placement. Material/Methods: Eighty premedicated ASA I-II patients (age 18-65 years) were randomized to receive dexmedetomidine (Group D=40) or remifentanil (Group R=40) before propofol induction. Group D received a 10-minute infusion (1 ?g.kg), while Group R received remifentanil (2 ?g.kg) over 60 seconds. Baseline systolic arterial pressure (SAP), diastolic arterial pressure (DAP), mean arterial pressure (MAP), heart rate (HR), and bispectral index (BIS) values were recorded before induction and at intervals up to 5 minutes after LMA placement. Results: Group R had significantly shorter eyelash reflex loss and LMA insertion times, but longer apnea duration. Ideal LMA insertion conditions, full chin opening, and no movement were more frequent in Group R (p<0.05). In Group D, HR was significantly lower than in Group R 1 minute before and after LMA insertion, but significantly higher in the 4th and 5th minutes after insertion (p<0.05). MAP in Group R was significantly lower than in Group D at 1 minute before and all times after LMA insertion (p<0.05). Conclusions: Administration of 2 ?g/kg remifentanil before 2.5 mg/kg propofol induction resulted in better hemodynamics, faster LMA insertion, and higher rates of optimal conditions compared to 1 ?g/kg dexmedetomidine © Med Sci Monit, 2025.
Keywords: Anesthesia, Spinal; Hemodynamics